Comparative Spectral Dynamic Analysis of Reinforcement with Buckling Restrained Braces and Fluid Viscous Dampers for an Irregular 11-Story Building - Olivares, Marco Antonio Ccota (2025)
This study presents a comparative spectral dynamic analysis between the use of Buckling Restrained Braces (BRB) and Fluid Viscous Dampers (FVD) in a configuration, applied to an irregular 11-story building. The effectiveness of both systems in reducing inelastic drifts and torsions was examined, considering the irregularities in height and plan. The results indicated that, without reinforcement, the building exhibited inelastic displacements that exceeded the permissible limit established by the Peruvian standardE.030. The implementation of BRB and FVD significantly reduced these displacements, improving the seismic response of the structure. This analysis allowed for the determination of which damping system provides better results in stiffness and seismic energy dissipation.